2000
DOI: 10.1530/eje.0.1420315
|View full text |Cite
|
Sign up to set email alerts
|

Defective nitric oxide synthesis: a link between metabolic insulin resistance, sympathetic overactivity and cardiovascular morbidity

Abstract: Epidemiological studies demonstrate an association between insulin resistance, hypertension and cardiovascular morbidity. In addition to its metabolic effects, insulin also has important cardiovascular actions. The sympathetic nervous system and the nitric oxide-L-arginine pathway have emerged as central players in the mediation of these actions. Over the past decade, the underlying mechanisms and the factors that may govern the interaction between insulin and these two major cardiovascular regulatory systems … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
83
0
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(86 citation statements)
references
References 118 publications
(47 reference statements)
2
83
0
1
Order By: Relevance
“…15,16 We therefore used a transgenic animal model to study the interaction between eNOS and insulin in the regulation of glucose metabolism. We found that eNOS Ϫ/Ϫ mice were insulin resistant, as evidenced by fasting hyperinsulinemia and glucose infusion rates during euglycemic clamp studies that were roughly 40% lower than in wild-type mice.…”
Section: Discussionmentioning
confidence: 99%
“…15,16 We therefore used a transgenic animal model to study the interaction between eNOS and insulin in the regulation of glucose metabolism. We found that eNOS Ϫ/Ϫ mice were insulin resistant, as evidenced by fasting hyperinsulinemia and glucose infusion rates during euglycemic clamp studies that were roughly 40% lower than in wild-type mice.…”
Section: Discussionmentioning
confidence: 99%
“…A more complex interpretation can be derived from the data from another study showing that ligation of the PIA2-genotype integrin could affect outside-in signalling efficacy with the consequence of more intense platelet-platelet interaction, but also increased adherence to immobilized adhesion molecules. Such events might take place not only in the large high flow vessels, but also in the nutritive microcirculation being regulatory part of the skeletal muscle energy metabolism [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…6 There is biochemical and physiological evidence suggesting that basal NO production and NO bioavailability are diminished in T2DM. [7][8] In physiological studies where vascular responses are mediated at least in part by NO, for example flow mediated vasodilatation (FMD), impaired responses are observed in subjects with T2DM. [9][10] Decreased NO bioavailability due to increased oxidative stress or quenching of NO by advanced glycation end-products may underlie the impairment in FMD.…”
Section: Introductionmentioning
confidence: 99%